تقويم بيانات التركيب العمري والنوعي لسكان محافظة عمران في الجمهورية اليمنية بحسب تعداد عام 2004م - الشرجبي, قاسم عبده علي (Journal of Amran University, 2023)
Data on the age and gender structure of a population is essential for planning for sustainable development and population estimates. However, population censuses are often subject to errors, which can make the data unreliable. The aim of this research was to evaluate the age and gender structure data for Amran Governorate, Yemen, as reported in the 2004 census. The research found that the data was heavily contaminated with errors, with an index of error of 58.29, which is much higher than the maximum acceptable limit. After applying adjustment procedures, the index of error was reduced to 26.60, which is closer to the acceptable minimum value. This suggests that the data is now of a good degree of accuracy and can be used for planning and research purposes. The research emphasizes the importance of evaluating gender and age structure data in population censuses using modern scientific methods before using the data.